2020
DOI: 10.1038/s41598-020-77679-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of influenza vaccination on cardiovascular diseases: a systematic review and meta-analysis

Abstract: Cardiovascular diseases (CVDs) are among the leading causes of mortality and morbidity worldwide. There are many contrasting ideas on the effectiveness of influenza vaccination on CVDs. This study aimed to investigate the association between influenza vaccination and the risk of CVDs. We systematically searched all PubMed/Medline, EMBASE, and the Cochrane library entries up to November 2019 for studies of influenza vs. the CVDs outcomes. We conducted a random-effects meta‐analysis using the inverse variance me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
(28 reference statements)
1
7
0
3
Order By: Relevance
“…For example, a recent meta-analysis of both randomized controlled trials and observational studies 7 showed that flu vaccination was associated with a lower risk of all-cause and cardiovascular (CV) mortality, as well as major CV events compared to controls. Other meta-analysis also reported similar findings of reduced CV and stroke risks 8-10 . Although reduction of flu infection is a possible mechanism, it has also been reported that flu vaccines may promote plaque stabilization via its interaction with the immune system 11,12 .…”
Section: Introductionsupporting
confidence: 62%
“…For example, a recent meta-analysis of both randomized controlled trials and observational studies 7 showed that flu vaccination was associated with a lower risk of all-cause and cardiovascular (CV) mortality, as well as major CV events compared to controls. Other meta-analysis also reported similar findings of reduced CV and stroke risks 8-10 . Although reduction of flu infection is a possible mechanism, it has also been reported that flu vaccines may promote plaque stabilization via its interaction with the immune system 11,12 .…”
Section: Introductionsupporting
confidence: 62%
“…Influenza vaccination is the primary strategy to reduce the lethality and morbidity of influenza infection [30]. Influenza vaccination may reduce subsequent risk for AMI or cardiovascular disease by 16% to 45% [31][32][33]. A population-based case-control study found that influenza vaccination could reduce the risk for AMI by 20% (adjusted OR: 0.80, 95% CI: 0.76-0.84, p<0.01) [32].…”
Section: Plos Onementioning
confidence: 99%
“…В работе [12] был проведен метаанализ связи между вакцинацией против гриппа и риском сердечно-сосудистых заболеваний на основе 17 исследований (6 рандомизированных контролируемых, 5 когортовых и 6 исследований случай-контроль) с общим количеством 180 043 случая и 276 898 контрольных участников. Вычисленные объединенные коэффициенты риска развития сердечно-сосудистых заболеваний после вакцинации против гриппа в рандомизированных контролируемых исследованиях составили 0,55.…”
Section: основная частьunclassified